Sindicalismo y lucha obrera en el textil andaluz a finales del siglo xix - Manuel Morales Muñoz (Cahiers de Civilisation Espagnole Contemporaine)
In order to deal with the wage cuts imposed by cotton textile entrepreneurs, the weavers and workers employed in Industria Malagueña, which was the largest manufacturing center in Andalusia, were protagonists of the most serious social conflicts that occurred in the last 19th century. Grouped in the ranks of socialist organizations, they tried to cope with employer pressure by resorting to strike, in initiatives that also had to resist coercions and threats from the authorities.